Invitation letter with a standardized form is a reliable tool to exclude increased risk patients from organized fecal immunological testing-based colorectal cancer screening program. Issue 12 (December 2018) - Sportes, Adrien; Catajar, Nathalie; Charles, Sébastien; Bejou, Bakthiar; Mary, Florence; Sabaté, Jean Marc; Le Mab, Guillaume; Benamouzig, Robert
Abstract: In Europe, screening guidelines for colorectal cancer (CRC) recommend colonoscopy for high-risk patients and fecal immunological testing (FIT) for the standard-risk group. Currently, there is not any validated screening tool to exclude high-risk patients. The aim of the study is to evaluate the validity of exclusion and evaluate the follow-up of patients identified as increased risk for CRC. In this retrospective study using a prospective database, patients at increased risk were identified using the standardized form and then excluded from the FIT screening invitation. A specific questionnaire was sent to all patients at increased risk in order to confirm the reason for the exclusion and evaluate their follow-up. Among 220 695 eligible individuals, 16 693 (7.5%) were excluded after being characterized at increased risk using the standardized form. The questionnaire was sent to these 16.693 excluded patients and completed by 5076 (30.7%) patients. Validity of exclusion was confirmed in 92% of cases. Endoscopic follow-up was in agreement with guideline in 89% of persons at increased risk (inflammatory bowel disease 93%, personal history of CCR 92%, of colonic polyps 82%, family history of CRC 77%). This study suggests that the standardized form is a reliable tool to correctly exclude from the screening program 92% of patients at increased risk for CRC.